Experimentation Of Mathematics Learning By Using Cooperative Model Type Two Stay Two Stray (Tsts) On The Subject Of A Circle Viewed From Student's Critical Thinking Ability In Grade Viii Of Smp N 1 Surakarta - Andhika, Niken Dwi, Rita P. Khotimah, S.Si., M.Sc (2013)
The purpose of this study are : (1) to analyze and examine the difference effect of using cooperative learning model type TSTS and conventional learning model to student's mathematics achievement, (2) to analyze and examine the difference effect of student's critical thinking ability to the student's mathematics achievement, (3) to analyze and examine interaction effect of using learning model and critical thinking ability of students to student's mathematics achievement .The population in this study are all students in VIII grade in SMP N 1 SURAKARTA 2011/2012 school year. Samples taken in this study are VIII G class as experiment class that given TSTS learning model and VIII H class as control class that given conventional learning model. The sampling technique used in this study is cluster random sampling. Collecting data method are used test method, questionnaire method, and documentation method. Data analysis technique using two-way analysis variance with unequal cell, a perquisite are need before, using the Liliefors test analysis method to test normality and Barlet method to test the homogeneity. From the analysis of the data with significance level 5% satisfied that: (1) There is no difference effect of using cooperative learning model type TSTS and conventional learning model to student's mathematics achievement with FA=1,51, (2) there is difference effect of students' critical thinking ability to student's mathematics achievement with FB=8,18, and(3) there is no interaction effect between learning model and student's critical thinking ability with FAB=0,46